Um estudo sobre rádios de software - Carvalho, Carolina Medeiros (2007)
Software Defined Radios, also named Software Radios, are a new technology where signal-processing software, running over a certain platform, perform functions that are done commonly by hardware. These radios play an important role in the current telecommunications context because they help to provide more flexibility and speed for the wireless communications systems development as they incorporate new functions, services and standards. This paper intends to characterize the software radios and expoe their general principles, advantages, applications and more common architectures. The hardware technologies that support software radios projects are also described. Besides, this paper proposes a simple application, the reception of AM signals, inclundig two different types of demodulation, to illustrate how they can be performed by the use of software simply by programming a digital signal processor. This paper also describes the computational simulations that were performed to demonstrate the success of the reception process. The simulation results are analysed by taking into account important topics of the digital signal processing theory.